Diseño y modelamiento de una planta para la producción de bioetanol a partir de la biomasa de microalga chlorella - Floriano Villacorta, Nélson Eugenio (2017)
The present research work aimed to design and model a plant for the production of bioethanol using as raw material the microalga Chlorella from the pre-treatment carried out with steam explosion where the thermal hydrolysis occurs, passing through the fermentation, distillation until the dehydration of the Bioethanol with molecular sieves. In turn, makes use of the software Super Pro Designer v9, having a daily production of anhydrous ethanol (Bioethanol) of 872 706,132 liters / day; thus making a profitable business as the total investment recovers after 0.68 years